Awareness and concern towards anesthesia among patients undergoing surgical procedure: A cross-sectional study at pre-anesthetic clinic of a Teaching Hospital - Moktan, Sushila Lama; Shrestha, Ujma; Sharma, Mona; Karki, Manan (Journal of Kathmandu Medical College, 2019)
Background: With the advent of anesthesia, surgery is no longer a race against the clock and surgeons. Many studies in the past have demonstrated limited knowledge among patients about various aspects of anesthesia. Objectives: To assess the awareness and concern of elective surgical patients towards anesthesia. Methodology: A cross-sectional questionnaire survey was conducted over two months’ period in adult patients of age eighteen years and above. Two hundred surgical patients accessing services at the pre-anesthesia check-up clinic were interviewed using 12 questions assessing demographic characteristics, educational status and their knowledge about anesthesia. Results: Out of 200 patients, only 32% knew that anesthesiologists provide anesthesia. It was found that 63% didn’t have any knowledge about the types of anesthesia. The most common fear among the participants about anesthesia was the fear of pain during surgery. Conclusion: The study showed poor knowledge of patients regarding anesthesia.